2019
DOI: 10.1152/ajpendo.00414.2018
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 release from muscles during exercise is stimulated by lactate-dependent protease activity

Abstract: IL-6 is secreted from muscles to the circulation during high-intensity and long-duration exercise, where muscle-derived IL-6 works as an energy sensor to increase release of energy substrates from liver and adipose tissues. We investigated the mechanism involved in the exercise-mediated surge in IL-6 during exercise. Using interval-based cycling in healthy young men, swimming exercise in mice, and electrical stimulation of primary human muscle cells, we explored the role of lactate production in muscular IL-6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 27 publications
6
56
0
1
Order By: Relevance
“…Hence, it could be expected that the increase in IL-10 levels would be reduced after the run; however, that was not the case, as IL-10 levels increased to the same level after the marathon in both groups of athletes. Further, exercise-induced increase in serum IL-6 levels is associated with intramuscular activation of metalloproteinases (MMP2 and MMPx); inactivation of these proteins blunts IL-6 release induced by swimming (Hojman et al, 2019). Interestingly, we here observed that the levels of TIMP-1, a tissue inhibitor of metalloproteinases, significantly decreased after the marathon and this effect was attenuated in runners after IPC.…”
Section: Discussionmentioning
confidence: 52%
“…Hence, it could be expected that the increase in IL-10 levels would be reduced after the run; however, that was not the case, as IL-10 levels increased to the same level after the marathon in both groups of athletes. Further, exercise-induced increase in serum IL-6 levels is associated with intramuscular activation of metalloproteinases (MMP2 and MMPx); inactivation of these proteins blunts IL-6 release induced by swimming (Hojman et al, 2019). Interestingly, we here observed that the levels of TIMP-1, a tissue inhibitor of metalloproteinases, significantly decreased after the marathon and this effect was attenuated in runners after IPC.…”
Section: Discussionmentioning
confidence: 52%
“…The relationship between the increased prevalence of TMD pain and moderate‐intensity exercise could partly be explained by the increased frequency of jaw‐clenching reported during intense exercise sessions and concentrating . Another mechanism may involve the increase in inflammatory cytokines following high‐intensity, long‐duration exercises . Many systematic reviews have reported on the low quality of evidence concerning the relationship between musculoskeletal disease symptoms and physical activity level.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 acts as both a proinflammatory cytokine and an anti-inflammatory myokine. 58,59 Skeletal muscle produces and releases significant levels of IL-6, which has been associated with stimulation of hypertrophic muscle growth and myogenesis through regulation of muscle satellite cells. 59 Paradoxically, deleterious actions for IL-6 have been proposed for atrophy and muscle wasting.…”
Section: Pemf and Inflammationmentioning
confidence: 99%